Son Yapılan Düzenlemeler Işığında AB Rekabet Hukuku ve Politikasına Genel Bir Bakış - Mustafa Ateş (Ankara Avrupa Çalışmaları Dergisi)
EC competition law and policy is seen one of the main tools for the creation of thecommon market and integrated Europe in every aspects. Fort this reason, EC paysutmost attention to the competition than some other policy areas. Since 1957, the dateof foundation of the Community, competition law and policy has been continuouslyrevised in a way that giving answer to the various requirements of the economy.Essentially, the most considerable changing in the Community competition law andpolicy was initiated late 1990's. In 1999, adopting the Regulation numbered 2790/1999,the EC reformed the regime of the exemption from anti-competitive behaviors ofundertakings. Community, aboliting the Regulation numbered 17/62, put into force in2004 the Modernization Regulation n ııııı bered 1/2003 dealing with the application ofthe antitrust provisions of the Treaty of Rome, namely Articles of 81 and 82. TheRegulation numbered 139/2004 on concentration, which was forınerly called "mergerregulation", was put into practice in 2004. Finally, the EC Commission launched adiscussion on the issue of the dominant position in 2005. By means of those reforms, thenational competition authorities and national courts have been giyen more power onthe applications of the Community competition rules. Iz ı other words, they have muchmore role and authority on the competition law and practice in the Communitydimension than they have ever been. Thus, the Commission is now able to deal with thegreater and more important anti-competitive conducts. This article aims to give a briefoverview of the Community competition law and policy with the framework of the recentreforms in the EC.